Harmonisation between Islamic law and science on DNA test of paternity: implications for connecting an illegitimate child to the male party - Haneef, Sayed Sikandar Shah (Malayan Law Journal Sdn Bhd, 2015)

(untitled)
Deoxyribonucleic acid (‘DNA’) testing of paternity has emerged as a conclusive scientific evidence of ascertaining paternity to overcome the problem of ‘paternity fraud’ and ‘misattributed paternity’ in the West. To harmonise it with old established common law principles of ‘presumption of paternity’ and ‘ex parte’ judgment for granting a woman her claim that her bastard child belongs to a certain accused, theWestern legal system has accommodated it within its law of evidence. In Islamic law, on the other hand, its reception as conclusive evidence in establishing or negating paternity is a mooting point among the jurists. Some have approved it partially others advocate its wholesale adoption. This presents another interesting case for the issue of harmonisation between Islam and science. In this divided juridical landscape, therefore, a selective approach will regard it in total harmony with Islamic law as argued by its supporters. However this approach will not only be questionable on methodological grounds but also polemical in terms of social acceptability. This paper argues for regulated proof-based approach to address its harmonisation with Islamic law, particularly to solve the problem of social location for some categories of illegitimate births and pregnancies.